EMPLOYEE PROPENSITY TO WITHHOLD EFFORT: A CONCEPTUAL MODEL TO INTERSECT THREE AVENUES OF RESEARCH - Kidwell, Roland E.; Bennett, Nathan (Academy of Management Review, 1993)
Roland E. Kidwell, Jr., Nathan Bennett, Employee Propensity to Withhold Effort: A Conceptual Model to Intersect Three Avenues of Research, The Academy of Management Review, Vol. 18, No. 3 (Jul., 1993), pp. 429-456